Nursing process applied to patient with tetralogy of Fallot - Jéssica Naiara de Medeiros Araújo; Andréa Tayse de Lima Gomes; Raianny Alves Costa; Ana Paula Nunes de Lima Fernandes; Vivivane Euzébia Pereira Santos; Allyne Fortes Vitor (Universidad de Alicante, 2017)
Objective: To describe the steps of the nursing process applied to patients with tetralogy of Fallot, based on NANDA-I, Nursing Interventions Classification (NIC) and Nursing Outcomes Classification (NOC). Method: This is a clinical case developed in a university hospital located in Northeast Brazil. It should be noted that this study was appreciated by the Ethics Committee of the Federal University of Rio Grande do Norte, which it approved it with number of Certificate of Presentation for Ethical Assessment: 07614812.6.0000.5537. Results: Among the four identified nursing diagnoses, has listed is a priority, which was intolerant of activity. The result, compromised moderately fatigue and activity of level, and interventions accounted for cardiac care: acute phase. Conclusions: After the execution of the care plan, it was observed that the actions taken have contributed significantly to the improvement of the health status of the patient, in order to contribute to increasing confidence and independence of it, despite the limitations inherent to the disease.